Epitranscriptomic regulation in fasting hearts: implications for cardiac health - Benák, Daniel; Holzerova, Kristyna; Hrdlicka, Jaroslav; Kolar, Frantisek; Olsen, Mark; Karelson, Mati; Hlavackova, Marketa (RNA biology, 2024)
Cardiac tolerance to ischaemia can be increased by dietary interventions such as fasting, which is associated with significant changes in myocardial gene expression. Among the possible mechanisms of how gene expression may be altered are epigenetic modifications of RNA - epitranscriptomics. N6-methyladenosine (m6A) and N6,2'-O-dimethyladenosine (m6Am) are two of the most prevalent modifications in mRNA. These methylations are reversible and regulated by proteins called writers, erasers, readers, and m6A-repelled proteins. We analysed 33 of these epitranscriptomic regulators in rat hearts after cardioprotective 3-day fasting using RT-qPCR, Western blot, and targeted proteomic analysis. We found that the most of these regulators were changed on mRNA or protein levels in fasting hearts, including up-regulation of both demethylases - FTO and ALKBH5. In accordance, decreased methylation (m6A+m6Am) levels were detected in cardiac total RNA after fasting. We also identified altered methylation levels in Nox4 and Hdac1 transcripts, both of which play a role in the cytoprotective action of ketone bodies produced during fasting. Furthermore, we investigated the impact of inhibiting demethylases ALKBH5 and FTO in adult rat primary cardiomyocytes (AVCMs). Our findings indicate that inhibiting these demethylases reduced the hypoxic tolerance of AVCMs isolated from fasting rats. This study showed that the complex epitranscriptomic machinery around m6A and m6Am modifications is regulated in the fasting hearts and might play an important role in cardiac adaptation to fasting, a well-known cardioprotective intervention.
Keywords: adenosin; RNA; Animals; Fasting; RNA, Messenger; messenger RNA; proteomika; Adenosine; Proteomics; krysa rodu Rattus; omezení příjmu potravy; zvířata; Rats